On the Strong Ratio Limit Property for Discrete-Time Birth-Death Processes - van Doorn, E.A. (Symmetry, Integrability and Geometry: Methods and Applications, 2018)
A sufficient condition is obtained for a discrete-time birth-death process to possess the strong ratio limit property, directly in terms of the one-step transition probabilities of the process. The condition encompasses all previously known sufficient conditions.